2019
DOI: 10.1029/2019jg005074
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Nitrogen Deposition Increases the Possibility of Macroalgal Dominance on Remote Coral Reefs

Abstract: Field surveys in the Xisha and Zhongsha archipelagos, in the midnorthern South China Sea, show macroalgal dominance on remote reefs that were previously dominated by corals. This study was conducted to investigate the underlying mechanisms of this phenomenon. Benthic composition analyses indicated that macroalgae that are rare on pristine reefs dominated 27% of 81 study sites, and live coral cover dropped to 16.3% in 2015. Nearly one third of corals came into direct contact with macroalgae. Further analyses on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…Hence, our results may reveal the dynamics of marine primary productivity and phytoplankton variability, highlighting anthropogenic P input as an important stress on remote and oligotrophic coral reefs. We also concluded that P could stimulate long‐term gross primary productivity in these coral reefs, in addition to the “atmospheric nitrogen hypothesis” proposed by Chen, Yu, et al (2019).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Hence, our results may reveal the dynamics of marine primary productivity and phytoplankton variability, highlighting anthropogenic P input as an important stress on remote and oligotrophic coral reefs. We also concluded that P could stimulate long‐term gross primary productivity in these coral reefs, in addition to the “atmospheric nitrogen hypothesis” proposed by Chen, Yu, et al (2019).…”
Section: Discussionsupporting
confidence: 75%
“…However, in light of the rich source of nitrogen for coral islands (D'Elia, 1988) and strong P limitations on Yongxing Island (Chen et al, 2016), we concluded that additional input of P due to guano exploitation should lead to increased marine primary productivity, as shown by coral δ 13 C. It is noteworthy, however, that sudden increases in P in seawater that exceed the threshold that coral reef systems can withstand could lead to the degeneration of coral reef ecosystems due to rapid and unchecked algal growth (Dunn et al, 2012; Ke et al, 2018; Martinez‐Escobar & Mallela, 2019). Field surveys of the Yongxing Islands, which were the major site of phosphate extraction, demonstrate that the reef hosts a much greater macroalgal cover than the other islands (Chen, Yu, et al, 2019). Furthermore, live coral cover, which is inversely correlated with macroalgal/turf cover (Guo et al, 2019), has decreased by nearly 20% on Yongxing Island over the past 30 years (Yu, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The Xisha Islands are rich in seabird populations (Xu et al, 2016), and nutrient subsidies from seabirds, therefore, may promote the growth of Halimeda. The most dominant herbivorous fish in the Xisha Islands seem to prefer turf algae over macroalgae (Chen et al, 2019). In contrast, Halimeda or other macroalgae species were rarely observed in reefs of the Nansha Islands, possibly because of the extremely low nutrient levels, high fish herbivory and lack of nutrient subsidies from seabirds, since there is no land for seabirds to nest on subtidal atoll reefs.…”
Section: Effective Regulation Of Environmental Factors Influencing mentioning
confidence: 96%
“…Evidence of nutrient subsidies from atmospheric nitrogen deposition and seabirds may help to explain this anomaly. Chen et al (2019) suggested that atmospheric nitrogen was the most likely potential source of nutrients for the promotion of macroalgal blooms in the Xisha Islands. In addition, nutrients from seabirds were found to promote the growth of Halimeda in the remote Chagos Archipelago of the central Indian Ocean (Benkwitt et al, 2019).…”
Section: Effective Regulation Of Environmental Factors Influencing mentioning
confidence: 99%
See 1 more Smart Citation